Trichoderma asperelloides Spores Downregulate dectin1/2 and TLR2 Receptors of Mice Macrophages and Decrease Candida parapsilosis Phagocytosis Independent of the M1/M2 Polarization - dos Santos, Andréa G.; Mendes, Érica A.; de Oliveira, Rafael P.; Faria, Ana M. C.; de Sousa, Aurizangela O.; Pirovani, Carlos P.; de Araújo, Fernanda F.; de Carvalho, Andréa T.; Costa, Marliete Carvalho; Assis Santos, Daniel; Montoya, Quimi V.; Rodrigues, Andre; et al. (Frontiers in Microbiology, 2017)
The intensive use of pesticides to control pests in agriculture has promoted several issues relating to environment. As chemical pesticides remain contraversial, biocontrol agents originating from fungi could be an alternative. Among them, we highlight biocontrol agents derived from the fungi genus Trichoderma, which have been documented in limiting the growth of other phytopathogenic fungus in the roots and leaves of several plant species. An important member of this genus is Trichoderma asperelloides, whose biocontrol agents have been used to promote plant growth while also treating soil diseases caused by microorganisms in both greenhouses and outdoor crops. To evaluate the safety of fungal biological agents for human health, tests to detect potentially adverse effects, such as allergenicity, toxicity, infectivity and pathogenicity, are crucial. In addition, identifying possible immunomodulating properties of fungal biocontrol agents merits further investigation. Thus, the aim of this study was to evaluate the effects of T. asperelloides spores in the internalization of Candida parapsilosis yeast by mice phagocytes, in order to elucidate the cellular and molecular mechanism of this interaction, as a model to understand possible in vivo effects of this fungus. For this, mice were exposed to a fungal spore suspension through-intraperitoneal injection, euthanized and cells from the peripheral blood and peritoneal cavity were collected for functional, quantitative and phenotypic analysis, throughout analysis of membrane receptors gene expression, phagocytosis ability and cells immunophenotyping M1 (CCR7 and CD86) and M2 (CCR2 and CD206). Our analyses showed that phagocytes exposed to fungal spores had reduced phagocytic capacity, as well as a decrease in the quantity of neutrophils and monocytes in the peripheral blood and peritoneal cavity. Moreover, macrophages exposed to T. asperelloides spores did not display the phenotypic profile M1/M2, and had reduced expression of pattern recognition receptors, such as TLR2, dectin-1 and dectin-2, all involved in the first line of defense against clinically important yeasts. Our data could infer that T. asperelloides spores may confer susceptibility to infection by C. parapsilosis.